2004
DOI: 10.1097/01.ju.0000127762.95045.93
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Bladder Dysfunction and Renal Function in Boys With Posterior Urethral Valves Based on Urodynamic Findings

Abstract: Bladder dysfunction may contribute to renal function impairment eventually but normal urodynamic findings do not preclude renal deterioration. It is likely that loss of compliance and detrusor overactivity would actually result in a valve bladder reaching its end point function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 19 publications
(30 reference statements)
1
28
0
Order By: Relevance
“…Historically, there have been concerns over the suitability of RTx for patients with ESRD resulting from LUTD because of the expected higher risks of UTI and other urological [2,3]. Although some authors confirmed that outcomes for RTx in children with LUTD were similar to those in children with normal lower urinary tracts [9][10][11][12][13][14], LUTD may have a significant impact on graft survival if not managed appropriately [4,15]. Low intravesical pressure with adequate bladder capacity and compliance, together with efficient drainage, should be achieved for a successful transplantation [11,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there have been concerns over the suitability of RTx for patients with ESRD resulting from LUTD because of the expected higher risks of UTI and other urological [2,3]. Although some authors confirmed that outcomes for RTx in children with LUTD were similar to those in children with normal lower urinary tracts [9][10][11][12][13][14], LUTD may have a significant impact on graft survival if not managed appropriately [4,15]. Low intravesical pressure with adequate bladder capacity and compliance, together with efficient drainage, should be achieved for a successful transplantation [11,12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The implications of bladder dysfunction in patients with valves are also well known. Poor bladder compliance and detrusor overactivity were shown to significantly correlate with renal functional impairment; however, normal urodynamic findings did not preclude upper tract deterioration [Ghanem et al 2004].…”
Section: Urodynamics In Intrinsic Bladder and Urethral Abnormalities mentioning
confidence: 99%
“…Urethral stricture may occur after valve ablation in a minority of cases and can be successfully treated endoscopically. Loop resection is associated with more strictures.Posterior urethral valves (PUVs) are the most common cause of congenital bladder outlet obstruction in boys [1,2] and cause renal failure in 25% to 30 % of cases before adolescence [2][3][4]. The severity of PUV varies from mild to lethal according to the degree of obstruction [5].…”
mentioning
confidence: 99%